The Great Gamble : The Soviet War in Afghanistan - Feifer, Gregory (Rawalpindi, Pakistan Services Book Club, 2010)
The Soviet war in Afghanistan was a grueling debacle that has striking lessons for the 21st century. Parallels between the Soviet invasion of Afghanistan and the U.S. invasions of Afghanistan and Iraq are impossible to ignore. The Soviet Union sent some of its most elite troops to unfamiliar lands to fight a vaguely defined enemy, which eventually defeated their superior numbers with unconventional tactics. Although the Soviet leadership initially saw the invasion as a victory, many Russian soldiers came to view the war as a demoralizing and devastating defeat, the consequences of which had a substantial impact on the Soviet Union and its collapse. NPR Moscow correspondent Gregory Feifer examines the conflict from the perspective of the soldiers on the ground. His extensive research includes eye-opening interviews with participants from both sides of the conflict, vividly depicting the invasion of a volatile country
Includes Illustration, Map, Note, Bibliography and Index
Keywords: Afghanistan -- Soviet Union -- Soviet Occupation of Afghanistan (1979-1989)